Penggunaan Media Sosial dan Pengetahuan Pelecehan Seksual pada Mahasiswa Kesehatan Masyarakat - Nafi’ah, Nadiyah; Aristi, Dela (Faculty of Health Sciences, Syarif Hidayatullah State Islamic University of Jakarta, 2023)
AbstractSexual harassment incidents can occur on college campuses. A lack of awareness might make it difficult to prevent sexual harassment. Students' frequent usage of social media can serve as a source of information about sexual harassment. The purpose of this study is to establish the description of social media use and knowledge about sexual harassment among students at UIN Syarif Hidayatullah Jakarta's Public Health Study Program. This is a descriptive study employing a cross-sectional study methodology, with 129 randomly selected respondents. The online questionnaire via Google Form was used to collect data. According to the findings, 55.8% of respondents had little understanding of sexual harassment, whereas 78.3% used social media extensively. The most popular social media channel for getting information on sexual harassment is Instagram (38.1%), while the most popular information provider is influencer/celebrity accounts (54.2%). Students are required to be able to select accurate and credible sources of information when researching sexual harassment.Keywords: Social Media, Knowledge, Sexual Harassment